Integration of a Return-to-Work Module in Cognitive Behavioral Therapy in Patients With Major Depressive Disorder and Long-Term Sick Leave—A Feasibility Study - Winter, Lotta; Geldmacher, Julia; Plücker-Boss, Katharina; Kahl, Kai G. (Frontiers in Psychiatry, 2020)
Objective Major depressive disorder (MDD) has a negative impact on individuals ability to work, and is often associated with long phases of sick leave. Consequently, interventions facilitating return to work in patients with MDD gained increased attention during last decades. We here report results of a feasibility study where a “return-to-work” (RTW) module published by Lagerveld and colleagues in the Netherlands was integrated in cognitive behavioral therapy in depressed patients with long-term sick leaves in Germany. Our study aimed to answer the following questions: Is RTW accepted by patients and therapists? Do RTW interventions lead to return-to-work? Do depressive symptoms improve? Methods Twenty patients with MDD (15 female; mean age, 45 ± 9 years) were included. Patients received cognitive-behavioral therapy with an integrated, standardized return-to-work module (W-CBT). Psychometric measurements included Beck Depression Inventory (BDI-2) and work ability index (WAI). Further, time until return-to-work was measured, and acceptability of W-CBT was assessed using visual analog scales and open questions. Results Mean sick leave days in depressed patients were 127 ± 97, and 75% of patients were sick leave for more than 6 weeks. After treatment, 11/20 patients had returned to their former occupation (55%), 5/20 were in occupational re-deployment or started a new job (25%), and 3/20 patients were still on sick leave (2/20; 10%) or received a pension (1/20; 5%). One patient dropped out. BDI-2 sum score improved from 23 ± 8 to 8 ± 5 (p < 0.001), and WAI improved from 28 ± 6 to 39 ± 7 (p < 0.001). Acceptability of W-CBT in patients and therapists was high. Conclusion We here demonstrate feasibility and acceptability of an RTW module integrated in standard cognitive behavioral therapy. W-CBT leads to improvement of work ability, paralleled by improvement of depressive symptoms. Despite the limitations of this uncontrolled study, the results propose that W-CBT may be feasible in the treatment of depressed patients with long sick leaves and justify a controlled trial evaluating the efficacy of W-CBT.